Persistent lip enlargement: An unusual presentation of lupus erythematosus - A. Nikoo; M. Daneshpazhooh; S. Fahim; A. Ghanadan; H. Mahmoudi; L. Izadi Firoozabadi (Wolters Kluwer, 2017)
Macrocheilia is a challenging problem with a variety of underlying causes that are both local and systemic, and granulomatous causes underlie the majority of cases. In this study, we report on a 31-year old man who presented with a chronic lower lip enlargement and a nodular submental erythematous lesion. He was otherwise clinically healthy. Laboratory test results were within the normal limit except for a positive anti-double stranded DNA test result. A diagnosis of cutaneous lupus erythematosus was made on the basis of histopathology and direct immunofluorescence. The lesions resolved dramatically after treatment with hydroxychloroquine. Lupus erythematosus should be considered when examining patients who present with chronic lip swelling.